2020
DOI: 10.1139/cjpp-2019-0299
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of olmesartan and l-carnitine on doxorubicin-induced cardiotoxicity in rats

Abstract: Doxorubicin (DOX), an anthracycline antibiotic, is an important antineoplastic agent due to its high antitumor efficacy in hematological as well as in solid malignancies. The clinical use of DOX is limited due to its cardiotoxic effects. The present study aimed to investigate the possible protective effect of olmesartan (Olm), l-carnitine (L-CA), and their combination in cardiotoxicity induced by DOX in rats. Male albino rats were randomly divided into seven experimental groups (n = 8): group I: normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…Noteworthy, plant derived-natural products have been extensively applied in improving DOX side effects. These agents enhance activity of antioxidant enzymes such as superoxide dismutase (SOD) and glutathione (GSH), while they diminish malondialdehyde (MDH) levels in preventing cardiotoxicity [95], through upregulation of Nrf2 signaling pathway [96].…”
Section: Doxorubicin: Cancer Resistance and Side Effectsmentioning
confidence: 99%
“…Noteworthy, plant derived-natural products have been extensively applied in improving DOX side effects. These agents enhance activity of antioxidant enzymes such as superoxide dismutase (SOD) and glutathione (GSH), while they diminish malondialdehyde (MDH) levels in preventing cardiotoxicity [95], through upregulation of Nrf2 signaling pathway [96].…”
Section: Doxorubicin: Cancer Resistance and Side Effectsmentioning
confidence: 99%
“…In accordance with our findings, it has been shown that DOX intoxication resulted in the elevation of cardiac MPO activity in DOX‐treated rats. [ 81,82 ] Our data revealed that treatment with TRE alone or in combination with DOX significantly reduced the myocardial MPO activities as compared to the DOX‐treated group. Hence, it is plausible that TRE decreased MPO‐induced ROS generation and, accordingly, reduced the myocardial damage in DOX‐treated mice.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, doxorubicin-induced oxidative stress can affect LPO and activate lysosomal enzymes, leading to promote the inflammation in heart tissue [ 15 ]. It has also been reported that the doxorubicin administration upregulates proinflammatory mediators of TNF- α , intercellular adhesion molecule-1 (ICAM-1), cyclooxygenase-2 (COX-2), TGF- β , nuclear factor-kappa B (NF- κ B), MPO, IL-1 β , and IL-6 levels in the cardiac cells [ 44 , 46 , 49 , 53 , 121 ]. ICAM-1 is a surface protein that is able to infiltrate leucocytes to the damaged regions of heart tissue [ 122 ].…”
Section: Discussionmentioning
confidence: 99%